(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The object of this paper is to analyze difference Human Resource allocation Guide, and suggest improved Human Resource allocation Guide to meet the owner’s needs. This paper analyzed the present situation of Human Resource allocation Guide by announcement and law through case study of construction management service about public office awarded by Public Procurement Service (PPS) from 2011 to 2013, and considered proper Human Resource allocation Guide in design process, during and after construction process. Based on the findings of current study, the following problems were identified; difference between announcement and legal Human Resource allocation, Human Resource allocation problem during the whole phase of project, and Human Resource allocation problem of work types. For the improvement, this paper suggests specifying minimum Human Resource requirement in RFP (Require For Proposal) so that it is available to manage flexible Human Resource allocation, proper Human Resource allocation Guide, in design process, to reduce the workload in construction process, and Human Resource allocation in construction process for appropriate compensation package. This study is anticipated to help the next following study to improve inefficient Human Resource allocation Guide.